SQL Injection: A Comprehensive Review of Methods and Future Directions (International Journal of Scientific Research in Science and Technology, 2025)
SQL Injection (SQLi) remains one of the most critical threats to web applications, enabling attackers to manipulate databases through malicious SQL queries. This paper reviews SQLi attack mechanisms, real-world impacts, detection techniques, and modern prevention strategies. By analyzing vulnerabilities, defensive tools (e.g., ORMs, WAFs), and emerging trends like AI-driven security, we provide a comprehensive guide to mitigating SQLi risks in software development.